(untitled) (Research, Society and Development, 2020)
Primary mucosal melanoma is a rare condition, corresponding to 1.4% of melanomas in general, being more common in the anorectal region due to the higher concentration of melanocytes. It is more prevalent between the sixth and eighth decade of life. It presents symptoms such as: local pain, enterorrhagia, hematochezia, presence of anal tumor mass, evacuation discomfort, which can generate prolapse during defecation due to the growth of the lesion. In face of vague and nonspecific signs and symptoms, the disease is characterized by having an unfavorable prognosis, as its diagnosis is usually late, being made in only 0.9 to 5% of cases, usually, due to the presence of complications. The identification of the disease is confirmed through histopathology. The present study describes the clinical case of a 69-year-old patient, who underwent, in the face of complaints, a polypectomy with biopsy that presented an intraepithelial malignancy of the anal canal with free margins, characterizing the procedure as a dressing.